An “in vivo” analysis of crafts practices and creativity—Why affordances provide a productive lens - Kimmel, Michael; Groth, Camilla (Frontiers in Psychology, 2023)
Scholars are increasingly recognizing that creativity is grounded in the active sensorimotor engagement with the environment and materiality. Affordances – recognizable pointers to action opportunities in the ecology – provide a helpful prism for analyzing how this happens. Creative practitioners, as they seek aesthetic opportunities or innovation, depend on their sensitivity towards potentialities in their action space. Presently, we apply a high-zoom lens to a crafts process, giving our micro-genetic research design an affordance focus. By investigating one of the authors, a ceramicist and a practitioner-researcher, through her process of making of a vase, we tracked how affordances are responded to, developed, shaped, invited or, where necessary, rejected, as the ceramicist “routes” her creative trajectory. Several insights emerge: (1) The ceramicist’s decisions – initially about general directions, then about aesthetic details – unfold while engaging with the clay; they emerge in stepwise fashion, but with a holistic orientation. (2) Choosing among affordances requires parallel sensitivities to object functionality, aesthetics and creativity, as well as technical feasibility; adhering to the proper technical procedure that provides the very basis for creatively relevant affordances to later arise. (3) While the hands and eyes engage with short-lived affordances the ceramicist must keep in view higher-timescale affordances that ensure a good task progression for making a vase, and affordances for the material’s overall “workability”. (4) The ceramicist typically relates to momentary affordances in light of expected as well as imagined others, to ensure a coherent end product. (5) Affordances contribute to material creativity in more ways than typically recognized in the literature. They range from serendipitous “finds” to options developed with a large degree of creative autonomy; affordances may also be indirectly invited and practitioners strategically change probability distributions as well as providing an enabling background for generative action. Thus, a crafts practitioner brings forth unconventional affordances through active engagement, using a mix of exploration, strategy, and imaginative potential. Affordance theorists err when stressing the possibility to just “find” creative options or that perceptual acuity is the sole skill.